(untitled) (Ibrahim Medical College Journal, 2015)
Subclinical hypothyroidism (SCH) may be of greater clinical importance in women with unexplained infertility, especially when the luteal phase is inadequate, and such patients should be investigated for thyroid dysfunction in detail. To date, studies investigating the association between SCH and infertility are still based on the high serum thyroid stimulating hormone (TSH) levels while some older studies are based on the presence of an abnormal serum TSH after a thyrotropin releasing hormone (TRH) stimulation test. The recommendation in the current guidelines to treat subclinical hypothyroidism is based on minimal evidence and it is thought that with treatment the potential benefits outweigh the potential risks. Thyroxine-replacement therapy should be started in patients with SCH caused by conditions which are at high risk of progression to overt hypothyroidism. Ibrahim Med. Coll. J. 2014; 8(1): 17-24